(untitled) (Medico Legal Update, 2019)
This study attempted to identify the smoking behavior, smoking motivation, stress and health promoting behaviors of college students and to analyze basic physical condition and to provide basic data for smoking cessation program of college students. The subjects of this study were 135 college students who were willing to quit smoking. Data collection period was collected from February 1, 2018 to June 30, 2018. Statistical methods used were frequency, mean, standard deviation, t-test and ANOVA. Also Pearson’s correlation analysis and regression analysis were used. Smoking motives are smoking behavior, key. Systolic blood pressure, hemoglobin, and smoking behavior were significantly correlated with CO 2 concentration. Body weight was significantly correlated with height, SBP, DBP, AST, ALT, ?-GTP, and CO 2 concentration and stress. There was a statistically significant correlation between SBP, DBP, ALT, hemoglobin, and hematocrit. Leukocyte was significantly correlated with hematocrit, and stress and ?-GTP were also significantly correlated. Health promotion activities showed a significant negative correlation with smoking motivation. Blood pressure, hemoglobin, platelet, and stress were found to have a significant effect on health promotion behaviors. Therefore, in order to prevent smoking of college students and help smoking cessation, basic physical condition is checked to promote health promotion, smoking cessation program should be developed to reduce smoking motivation.